PROSES KOGNITIF SISWA SEKOLAH DASAR DALAM MEMAHAMI MATERI PECAHAN DITINJAU DARI STIFIN FRAMEWORK: THINKING DAN FEELING - Kamid Kamid; Sutrisno Sutrisno; Khairul Anwar; Rina Kusuma Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
AbstractThe understanding of students, their learning methods, and cognitive characteristics are important aspects of classroom learning management. Fractional math problems require reasoning and mathematical logic, so to complete the gap in previous research, namely how types of intelligence form patterns of student thought processes, this study examines the level of student understanding and problem-solving strategies for fractions based on STIFin intelligence characteristics. This research uses a mixed-method approach in data collection. The research instrument uses the Fraction Sense Test (FST) and interviews and STIFin tests. The study involved 16 fourth-grade students of SD 47 Kota Jambi. The results showed that students with the thinking intelligence type scored the highest compared to sensing, intuiting, and feeling. Furthermore, there are four strategies students use in developing problem-solving strategies for fractions: (1) comparing fractions using other simple benchmark fractions like ½, (2) comparing fractions based on the denominator and numerator, (3) creating a fraction representation in the form of flat shapes to understand and compare fractions.